Indirect comparison of the efficacy and safety of alirocumab and evolocumab: a systematic review and network meta-analysis. Issue 3 (10th April 2020) - Guedeney, Paul; Sorrentino, Sabato; Giustino, Gennaro; Chapelle, Celine; Laporte, Silvy; Claessen, Bimmer E; Ollier, Edouard; Camaj, Anton; Kalkman, Deborah N; Vogel, Birgit; De Rosa, Salvatore; Indolfi, Ciro; et al.
Abstract: Aims: Although alirocumab and evolocumab have both been associated with improved outcomes in patients with dyslipidaemia or established atherosclerotic cardiovascular disease, data on their respective performances are scarce. This study aimed at providing an indirect comparison of the efficacy and safety of alirocumab vs. evolocumab. Methods and results: We conducted a systematic review and network meta-analysis of randomized trials comparing alirocumab or evolocumab to placebo with consistent background lipid-lowering therapy up to November 2018. We estimated the relative risk (RR) and the 95% confidence intervals (CIs) using fixed-effect model in a frequentist pairwise and network meta-analytic approach. A total of 30 trials, enrolling 59 026 patients were included. Eligibility criteria varied significantly across trials evaluating alirocumab and evolocumab. Compared with evolocumab, alirocumab was associated with a significant reduction in all-cause death (RR 0.80, 95% CI 0.66–0.97) but not in cardiovascular death (RR 0.83, 95% CI 0.65–1.05). This study did not find any significant differences in myocardial infarction (RR 1.15, 95% CI 0.99–1.34), stroke (RR 0.96, 95% CI 0.71–1.28), or coronary revascularization (RR 1.13, 95% CI 0.99–1.29) between the two agents. Alirocumab was associated with a 27% increased risk of injection site reaction compared to evolocumab; however, no significant differences were found in terms of treatment discontinuations, systemic allergic reaction, neurocognitive events, ophthalmologic events, or new-onset of or worsening of pre-existing diabetes. Conclusion: Alirocumab and evolocumab share a similar safety profile except for injection site reaction. No significant differences were observed across the efficacy endpoints, except for all-cause death, which may be related to the heterogeneity of the studied populations treated with the two drugs.